Cerebellocerebral Diaschisis Is the Likely Mechanism of Postsurgical Posterior Fossa Syndrome in Pediatric Patients with Midline Cerebellar Tumors - Miller, N.G.; Reddick, W.E.; Kocak, M.; Glass, J.O.; Löbel, U.; Morris, B.; Gajjar, A.; Patay, Z. (American Journal of Neuroradiology, 2010)
BACKGROUND AND PURPOSE: PFS occurs in approximately 25% of pediatric patients receiving surgery for midline posterior fossa tumors. Increasing evidence suggests that PFS represents a complex supratentorial cortical dysfunction related to surgery-induced disruption of critical cerebellocerebral connections. The purpose of this study was to determine whether a consistent surgical damage pattern may be identified in patients with PFS by early postoperative anatomic imaging analysis of the pECP and to test whether DSC can detect corresponding changes in cerebral cortical perfusion to indicate a secondary, remote functional disturbance, which could suggest a diaschisis-like pathomechanism. MATERIALS AND METHODS: Eleven patients with postoperative PFS were evaluated retrospectively and were paired with age- and sex-matched control subjects in whom PFS did not develop. MR imaging work-up included DSC within 3 to 4 weeks after surgery as well as early postoperative anatomic imaging to evaluate components of the pECP. RESULTS: DSC showed significant decreases in CBF within frontal regions (P < .05) and a trend to global cerebral cortical hypoperfusion in patients with PFS. Logistic regression analysis suggested a strong (potentially predictive) relationship between bilateral damage to pECP and the development of PFS (P = .04). CONCLUSIONS: Our data suggest that the primary cause of PFS is the bilateral surgical damage to the pECP. This leads to a trans-synaptic cerebral cortical dysfunction (a form of bilateral crossed cerebellocerebral diaschisis), which manifests with DSC-detectable global, but dominantly frontal, cortical hypoperfusion in patients with patients with PFS compared with age- and sex-matched control subjects. ADCapparent diffusion coefficientAIFarterial input functionCBFcerebral blood flowCBVcerebral blood volumeCCDcerebellocerebral diaschisisDSCdynamic susceptibility-weighted contrast-enhanced perfusion MR imagingFLAIRfluid-attenuated inversion recoveryGBCAgadolinium-based contrast agentPDproton-attenuationpECPproximal efferent cerebellar pathwayPFSposterior fossa syndromeROIsregions of interest.